Relationship between antioxidant and anxiolytic activity of standardized extracts of Melissa officinalis and Rosmarinus officinalis - María Eugenia Letelier; Carlos Andrés Gallardo-Garrido; Carmen Luz Villar-Bustamante; Gabriela Díaz-Véliz (International Journal of Phytomedicine, 2015)
All diseases, especially those neurological pathologies (Depression, anxiety, Alzheimer and Parkinson’s diseases, etc) are described to be associated to oxidative stress. An increased concentration of metal ions in neurons of patients could be, at least in part, the cause of this oxidative stress. Reduced metal ions generate ROS through Haber-Weiss and/or Fenton reactions. By other hand, psychotropic effects of diverse plants have been described, between them Melissa officinalis and Rosmarinus officinalis. Pharmacological studies about the beneficial effects of these plants are scarce, especially those about Rosmarinus officinalis. In this work, a correlation between biological antioxidant activity of these plants and their anxiolytic activity was studied. Results show that this correlation seems to occur, and the pharmacokinetic and pharmacodynamic importance of this phenomenon is discussed.